Practices of Social Studies Pre-Service Teachers in Balancing Roles During and After the Remote Learning Setup - Heart L. Mellizo; John Erwin Prado Pedroso (RADINKA JAYA UTAMA PUBLISHER, 2023)
Throughout 11 countries across Asia, Africa, Europe, the Arab region, and Latin America, the Responses to Educational Disruption Survey (REDS) report found that despite the disruptions and the fact that learning institutions did not consider remote education as an integral part of teaching, teachers, principals, and students needed to adapt to alternative teaching methods for teaching and learning to continue. The limits of recent research conducted in the Philippines revolve around the time of learning during the pandemic and with guidelines being set to conduct in-person classes after about three years in a remote learning setup. This study aims to compare how students have adapted to their roles in the latter relative to the post-pandemic setup. The study made use of a qualitative descriptive research design. Six (6) informants of the study are Social Studies pre-service teachers as identified through a purposive sampling technique. The questionnaire was duly checked and attested by the experts in qualitative research and then distributed to the informants. A thematic analysis was employed in the data analysis procedure of this study. This study provides significant adaptive practices that are relevant today, particularly in the post-remote learning setup.